PENERAPAN SHAKER EXERCISE DAN LATIHAN MENELAN DENGAN JELLY TERHADAP KEMAMPUAN MENELAN PADA PASIEN STROKE DI RSUD SUNAN KALIJAGA DEMAK - Ainnur Rahmanti; Atika Febri D (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Difficulty swallowing is caused by impaired muscle coordination, muscular weakness of the tonus swallowing which is associated with impaired hemisphere function, nuclei of the brain nerve fibers that confer and muscles chew and swallow. The purpose of this case study is to describe the application of Shaker exercise and jelly in swallowing exercises in the stroke patients in the Hospital Sunan Kalijaga Demak. This method of research is descriptive using a case study approach. The subject in this study were two patients with stroke difficulty swallowing, patients in rehabilitation, not experiencing a loss of consciousness and a patient's vital signs of stable. Ingested ability is measured with The Royal Adelaide Prognostic Index For Dysphagic Stroke (RAPIDS). Results of the analysis showed that there was increased ability to swallow after intervention. In the subject I before the 81 scorecard intervention (low aspiration risk) experienced increased scorecard to 86 (low aspiration risk). Meanwhile, in the subject II before the intervention of Scorecard 82 (low aspiration risk) experienced a better namely 91 (low aspiration risk). This research recommends nurses can apply shaker exercise and jelly in swallowing exercises in stroke patients with difficulty swallowing